Classification of Specialized Texts Based on Their Terminologies - Guantiva Acosta, Ricardo; Cabré Castellví, Maria Teresa; Casrellà Lidon, Josep Maria (Íkala, Revista de Lenguaje y Cultura, 2008)
This article deals with the classification of specialized texts based on the linguistic typology of terminology units and their density within the texts. With this in mind, we review some basic concepts of text linguistics in the context of specialized communication (general texts and specialized texts) in order to establish the differences between communicative registers. We also examine the concept of terminology unit, using the Communicative Theory of Terminology (CTT). In terms of the materials used, we worked with a text related to the topic of ''human genome'', classified into different levels of specialization. To this respect we also offer a brief description of the computer analysis carried out in the extraction and detection of the terminology units within the texts, and we present the results, classifying the texts into different levels of specialization. Received: 19-11-07 / Accepted: 01-03-08 How to reference this article: Guantiva Acosta, R.; Cabre Castellvi, M. T. & Castella Lidon, J. M. (2008). Clasificación de textos especializados a partir de su terminología. Íkala. 13(1), pp.15-39.